THE EFFECTIVENESS OF PROJECT-BASED E-LEARNING TO IMPROVE ICT LITERACY - Eliana, E. D. S.; Senam, Senam; Wilujeng, I.; Jumadi, Jumadi (Jurnal Pendidikan IPA Indonesia, 2016)
This study aims to reveal the effectiveness of science teaching based on project-based learning to improve ICT literacy learners in the junior high school with the category of high, medium and low. This research uses descriptive method to describe the studentsâ equipness of ICT literacy in the science learning based on the project-based learning that is integrated with e-learning. All of the population in this study are junior high school of curriculum pilot project in 2013 in Singkawang. The sampling in this study uses stratified random sampling to determine three of the four schools that represent the school with a category of high, medium and low based on the National Examination score on 2015, namely, SMPN 1 Singkawang, SMPN 3 Singkawang, and SMPN 7 Singkawang and from each school are randomly selected one class. The data collection is done by the observation and questionnaires of the studentsâ equipness in ICT literacy with effective criteria only if it is in a good or excellent criteria. Based on the analysis, project-based learning science-based learning is effective in equipping ICT literacy learners at junior high school Â at the categories of high, medium and low.